Inclusive Policy in Higher Education Institutions of Ukraine: Current Approaches and Experiences of Implementation - Tsymbaliuk, Svitlana (Educological discourse, 2026)
The development of higher education involves implementing social inclusion principles, ensuring equal access to quality education for all citizens. The purpose of the article is to analyse the state and specific features of implementing inclusive policies and practices in higher education institutions in Ukraine, as well as to identify the strengths and weaknesses of existing approaches. The study is based on the results of a survey conducted among academic staff, heads of structural units, and students from various types and ownership forms of higher education institutions in Ukraine. A total of 821 respondents participated. Both quantitative and qualitative research methods were applied for a comprehensive analysis of inclusive policies and practices. The results show that Ukrainian higher education institutions have achieved significant progress in certain areas. In particular, a high level of adaptability in the educational process was observed, reflected in the use of flexible learning formats and opportunities for demonstrating knowledge in various ways, which accommodate the individual needs of students. The development of institutional policies and mechanisms, such as budgetary quotas, is an important achievement that demonstrates the systematic efforts of the state and educational institutions. Positive experience was also recorded in implementing mental health support and psychological assistance measures, which is especially relevant under martial law. However, the study also revealed systemic gaps and barriers hindering the effective implementation of inclusive policies and practices. The most significant issue is the low accessibility of information for persons with disabilities and foreign language students, which poses a serious challenge to the principles of inclusiveness. A high percentage of “difficult to answer” responses regarding reporting, funding, and the availability of responsible persons indicates a lack of systematic monitoring and transparent communication. Another serious obstacle is the insufficient professional training of academic staff in the field of inclusion. For the effective realisation of social inclusion priorities, it is crucial to address the identified shortcomings in transparency, information accessibility, institutionalisation of responsible positions, and staff training. Future research may focus on assessing the impact of implemented inclusive practices on students’ academic performance and social adaptation, analysing specific barriers and causes of poor communication and motivation, and comparing Ukraine’s experience with that of other countries to develop effective policy recommendations.